Global competitiveness of European surface technology. Part 2: challenges to and future development of the surface finishing sector. (2nd January 2021) - Leisner, P.; Larson, C.; Nielsen, L. P.; Müller, S.; Hansal, W.; Puippe, J.-C.; Zielonka, A.
ABSTRACT: Based on an analysis of the competitiveness of the European surface finishing industry, challenges are discussed and future directions for remaining competitive are recommended. The European surface finishing sector should prioritise advanced production technology for new high-tech and high added value products, and take advantage of disruptive changes in society and technology shifts where completely new areas of application of surface technology can arise. To be successful, surface finishers should meet expectations on price, quality, short lead time, innovation ability, complying with legislation, and brand equity. This should be accomplished by increased automation, closer cooperation within the value chain, and improved competence supply. Such a development is extra challenging for the many small-size sub-contractors in the sector. Basically, improved education and improved organisation between applied research, product development, production development and manufacturing are needed. Therefore, the need is strong for pan-European actions to coordinate and expand education on all levels. Higher competence leads to better reliability, quality, and cost-efficiency. Furthermore, the innovation capability will benefit from improved communication between the different actors in the value chain. Finally, coordinated actions are needed to market surface technology/finishing as an interesting and rewarding field in which to make a career. Europe has a strong tradition in surface finishing and the sector is characterised by a significant diversity. The right competence supply and organisation can make 'cooperative diversity' a European stronghold.